Instructional Choice: An Effective, Efficient, Low-Intensity Strategy to Support Student Success. (December 2018) - Lane, Kathleen Lynne; Menzies, Holly M.; Ennis, Robin Parks; Oakes, Wendy Peia; Royer, David James; Lane, Katie Scarlett
Instructional choice is a practical strategy for increasing student engagement and decreasing challenging behavior. In this article, we describe a step-by-step process for incorporating instructional choice into classroom activities, with teaching tips to assist with successful implementation. Throughout the article, we offer lessons from the field featuring the perspectives of practitioners and students who have used instructional choice in classrooms that include students at risk for emotional and behavioral disorders.